S Strategi Penanganan Pembiayaan Bermasalah Pada BPRS Daya Artha Mentari Pasuruan: Strategi Penanganan Pembiayaan Bermasalah - Siti Ilfiah; Saiful Bakhri; Ilham Wahyudi (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
Problematic financing can affect the income of BPRS Daya Artha Mentari Pasuruan. This requires treatment to overcome problematic financing. The aim of this research is to find out the strategy for handling problematic financing carried out by BPRS Daya Artha Mentari Pasuruan. This research is field research with a qualitative approach. The research results discuss problematic financing caused by two factors, namely internal factors (coming from BPRS Daya Arha Mentari Pasuruan) and external factors (coming from members). Handling problematic financing at BPRS Daya Arha Mentari Pasuruan by contacting members by telephone, SP warnings, billing directly to the customer's location, conducting customer negotiations through rescheduling, Reconditioning, Restructuring, and confiscation of collateral.